2020
DOI: 10.3389/fpls.2020.00374
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Light Response of Leaf-Scale Water-Use Efficiency and Its Interrelationships With Photosynthesis and Stomatal Conductance in C3 and C4 Species

Abstract: Light intensity (I) is the most dynamic and significant environmental variable affecting photosynthesis (A n), stomatal conductance (g s), transpiration (T r), and water-use efficiency (WUE). Currently, studies characterizing leaf-scale WUE-I responses are rare and key questions have not been answered. In particular, (1) What shape does the response function take? (2) Are there maximum intrinsic (WUE i ; WUE i−max) and instantaneous WUE (WUE inst ; WUE inst−max) at the corresponding saturation irradiances (I i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 44 publications
6
24
1
2
Order By: Relevance
“…The overestimation of A nmax by NH model found in this study is consistent with the previous reports (e.g., Calama et al., 2013 ; dos Santos et al., 2013 ; Lobo et al., 2014 ; Ježilová et al., 2015 ; Mayoral et al., 2015 ; Ogawa, 2015 ; Park et al., 2016 ; Quiroz et al., 2017 ; Poirier-Pocovi et al., 2018 ; Ye et al., 2020 ). The accurate returning of A nmax by Ye model found in this study is consistent with previous studies using Ye model for various species under different environmental conditions (e.g., Wargent et al., 2011 ; Zu et al., 2011 ; Xu et al., 2012a ; Xu et al., 2012b ; Lobo et al., 2014 ; Xu et al., 2014 ; Song et al., 2015 ; Chen et al., 2016 ; Ye et al., 2019 ; Yang et al., 2020 ; Ye et al., 2020 ). The robustness of Ye model has also been validated for microalgae observations, including four freshwater and three marine microalgae species ( Yang et al., 2020 ).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The overestimation of A nmax by NH model found in this study is consistent with the previous reports (e.g., Calama et al., 2013 ; dos Santos et al., 2013 ; Lobo et al., 2014 ; Ježilová et al., 2015 ; Mayoral et al., 2015 ; Ogawa, 2015 ; Park et al., 2016 ; Quiroz et al., 2017 ; Poirier-Pocovi et al., 2018 ; Ye et al., 2020 ). The accurate returning of A nmax by Ye model found in this study is consistent with previous studies using Ye model for various species under different environmental conditions (e.g., Wargent et al., 2011 ; Zu et al., 2011 ; Xu et al., 2012a ; Xu et al., 2012b ; Lobo et al., 2014 ; Xu et al., 2014 ; Song et al., 2015 ; Chen et al., 2016 ; Ye et al., 2019 ; Yang et al., 2020 ; Ye et al., 2020 ). The robustness of Ye model has also been validated for microalgae observations, including four freshwater and three marine microalgae species ( Yang et al., 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…For the first time, our study discloses the previously widely reported overestimation of J max (and A nmax ) by the NH model is linked to its overestimation of J C-max but not J O-max . The overestimation of A nmax by NH model found in this study is consistent with the previous reports (e.g., Calama et al, 2013;dos Santos et al, 2013;Lobo et al, 2014;Jezǐlováet al, 2015;Mayoral et al, 2015;Ogawa, 2015;Park et al, 2016;Quiroz et al, 2017;Poirier-Pocovi et al, 2018;Ye et al, 2020). The accurate returning of A nmax by Ye model found in this study is consistent with previous studies using Ye model for various species under different environmental conditions (e.g., Wargent et al, 2011;Zu et al, 2011;Xu et al, 2012a;Xu et al, 2012b;Lobo et al, 2014;Xu et al, 2014;Song et al, 2015;Chen et al, 2016;Ye et al, 2019;Yang et al, 2020;Ye et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations